La dialettica dell’immagine terroristica: Baudrillard contro Baudrillard - Tramontana, Antonio (Mediascapes journal, 2017)
Starting from Baudrillard’s The Spirit of Terrorism, the aim of this paper is to understand the nature of the power of the 9/11 Attack. According to Baudrillard this power in based on the terrorist ability to combine the modern resources with a highly symbolic weapon (their death). Thus, “the white magic of the cinema and the black light of terrorism” are unified into a unique image. This cohabitation is the heart of the Baudrillard’s analysis on terroristic image. Through Benjamin’s “Dialectical Image”, I will analyze three terroristic images (the collapse of the World Trade Center, the destruction of Mosul Museum artifacts by ISIS, and the Charlie Hebdo shooting) with the purpose to focus on a new social form of experience.